Celebrating Adam Watkins' 7th Birthday at Chuckie Cheeses - Watkins, Howard::::::::: (1985)
Waitress leading singing of Happy Birthday to Adam with Chuckie Cheese in costume; Adam Watkins, Seth Tilley and Art Wille